An international view of true and fair accounting - Parker, R. H. (Robert Henry); Nobes, C. W. (London ; New York : Routledge, 1994)
This book is about the "true and fair view" which is a central but mysterious feature of financial reporting.
Keywords: Finance; Economics; Financial statements; Financial statements; Disclosure in accounting